Local coarsening method for surface of copper-clad ceramic substrate
By optimizing the steps and parameters of the local roughening process of copper-clad ceramic substrate, complexity and control problems in the prior art are solved, and the local roughening efficiency and quality of the surface of copper-clad ceramic substrate is improved.
Patent Information
- Application Number
- CN202411469623.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-14
AI Technical Summary
The prior art has problems such as complexity and inability to accurately control the local roughening range of copper-clad ceramic substrates in the local roughening process, which affects the control of roughness and product quality.
By defining the steps, exposure parameters and sequence of the surface of the copper-clad ceramic substrate, including chemical cleaning, filming, exposure, development and roughening treatment, using acidic oil degreasing agents, photosensitive films, local exposure and hydrogen peroxide sulfate water using acidic oil removal agents, photosensitive films, local exposure and hydrogen peroxide sulfate. System potions and other technical means to optimize exposure energy and processing parameters.
The local roughness of the surface of the copper-clad ceramic substrate is significantly improved, the coarse efficiency and quality are improved, and the precise roughening of the local areas is achieved.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper-clad ceramic substrate research, and relates to a method for locally roughening the surface of a copper-clad ceramic substrate. Background Art
[0002] With the development of new energy vehicles, the development of power semiconductor modules has also advanced by leaps and bounds, and packaging technology has become increasingly sophisticated, and the requirements for heat dissipation copper-clad ceramic substrates have become increasingly higher. At present, some packaging processes have increasingly higher requirements for the roughness of the surface of copper-clad ceramic substrates in order to increase the bonding strength with the resin board, but too high roughness will affect the wire bonding ability of the product. Therefore, increasing the roughness of local areas is an urgent method.
[0003] The prior art solution discloses a local roughening production process for a lead frame based on plating first and then etching, including the following steps divided into primary treatment and secondary treatment, and finally using a local roughening method to cover the lead frame area that needs to be locally roughened, and then using a roughening solution to spray the unobstructed area of the lead frame, the ingredients in the solution can cause a roughening reaction on the surface of the area; post-roughening treatment: after the roughening is completed, the lead frame needs to be cleaned to remove residual roughening solution and impurities.
[0004] The prior art solution discloses a local area roughening electroplating strip with a shielding effect, comprising an electroplating strip body and a shielding shell, wherein the surface of the electroplating strip body is shielded with the shielding shell, the outer side of the first lining roll is shielded with a raw material roll, the outer side of the second lining roll is shielded with a corrosion material roll, and an open slide groove is opened on one side of the shell body. The area of the electroplating strip body that needs to be roughened is exposed in the open slide groove through the shielding shell, and other areas are shielded. The open slide groove facilitates the addition of neutral acid substances to the surface of the electroplating strip body, and the area that needs to be roughened is micro-corroded by chemical reaction, thereby forming a roughening effect in the target area.
[0005] However, the current roughening method is too complicated and cannot accurately control the scope of local roughening, and the local roughness is difficult to control. Therefore, it is urgent to design a local roughening method for the surface of copper-clad ceramic substrates to overcome the defects of existing technologies and meet practical application needs. Summary of the invention
[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for local roughening of the surface of a copper-clad ceramic substrate. In the present invention, by limiting the steps, exposure parameters and sequence of the local roughening method of the surface of the copper-clad ceramic substrate, the roughness of the local position of the surface of the copper-clad ceramic substrate is greatly improved, and it is no longer necessary to roughen only the entire surface of the copper-clad ceramic substrate, thereby improving the roughening efficiency and the roughening quality.
[0007] To achieve this object, the present invention adopts the following technical solutions:
[0008] The present invention provides a method for local roughening of the surface of a copper-clad ceramic substrate, the local roughening method comprising:
[0009] The copper-clad ceramic substrate to be roughened is subjected to chemical cleaning treatment, film laminating treatment, exposure treatment, development treatment and roughening treatment in sequence to obtain a locally roughened copper-clad ceramic substrate.
[0010] Among them, the exposure energy of the exposure treatment is 600-700mj, for example, it can be 600mj, 610mj, 620mj, 630mj, 640mj, 650mj, 660mj, 670mj, 680mj, 690mj, 700mj, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0011] In the present invention, by limiting the steps, exposure parameters and sequence of the local roughening method of the surface of the copper-clad ceramic substrate, the roughness of the local position of the surface of the copper-clad ceramic substrate is greatly improved, and it is no longer necessary to roughen only the entire surface of the copper-clad ceramic substrate, thereby improving the roughening efficiency and the roughening quality.
[0012] It should be noted that the chemical cleaning treatment in the present invention is mainly used to clean oil, oxides, etc. on the surface of the copper-clad ceramic substrate to provide better adhesion for the photosensitive dry film; the coating layer of the photosensitive film can be one layer or multiple layers; the exposure treatment is mainly to locally expose the product coated with the photosensitive dry film or the photosensitive wet film, and to expose and cure the areas that do not need to be roughened to achieve the purpose of local exposure; the development treatment is mainly 4. to develop the exposed product, to show the areas that need to be roughened, and finally to perform the roughening treatment.
[0013] As a preferred technical solution of the present invention, the chemical cleaning treatment is carried out in the following manner:
[0014] The roughened copper-clad ceramic substrate is cleaned by using a cleaning liquid.
[0015] As a preferred technical solution of the present invention, the cleaning liquid is an acidic degreasing agent.
[0016] It should be noted that the acidic degreasing agent used in the present invention can achieve a better cleaning effect on the copper-clad ceramic substrate compared to the alkaline degreasing agent.
[0017] Preferably, the acidic degreasing agent includes any one of sulfuric acid, phosphoric acid, nitric acid or citric acid.
[0018] Preferably, the cleaning speed of the cleaning liquid is 1 to 1.5 mm / min, for example, it can be 1 mm / min, 1.1 mm / min, 1.2 mm / min, 1.3 mm / min, 1.4 mm / min, 1.5 mm / min, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0019] The cleaning speed of the cleaning liquid in the present invention is 1-1.5 mm / min, because within this range, the cleaning effect on the copper-clad ceramic substrate can be better. If it is not within this range, the cleaning effect may be poor.
[0020] As a preferred technical solution of the present invention, the film pasting process is carried out in the following manner:
[0021] A photosensitive film is applied to the surface of the copper-clad ceramic substrate to be roughened after chemical cleaning.
[0022] As a preferred technical solution of the present invention, the photosensitive film is a photosensitive dry film or a photosensitive wet film.
[0023] Preferably, the lamination temperature of the photosensitive dry film is 90-110°C, for example, it can be 90°C, 92°C, 94°C, 96°C, 98°C, 100°C, 102°C, 104°C, 106°C, 108°C, 110°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] Preferably, the lamination pressure of the photosensitive dry film is 5-10 KPa, for example, 5 KPa, 6 KPa, 7 KPa, 8 KPa, 9 KPa, 10 KPa, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] The laminating temperature of the photosensitive dry film in the present invention is 90-110° C. and the laminating pressure is 5-10 KPa, because within this range, the adhesion of the film can be sufficient. If it is not within this range, the adhesion of the film may be poor.
[0026] Preferably, the photosensitive wet film is applied by screen printing.
[0027] It should be noted that the specific operation steps of screen printing are not particularly limited in the present invention, and those skilled in the art can make adaptive selections according to actual conditions.
[0028] Preferably, the mesh number of the screen used in the screen printing is 200-300 meshes, for example, it can be 200 mesh, 220 mesh, 240 mesh, 260 mesh, 280 mesh, 300 mesh, etc., but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] The mesh number of the screen used for screen printing in the present invention is 200-300 meshes, because within this range, the thickness uniformity of the copper-clad ceramic substrate can be better. If it is not within this range, the thickness may be uneven.
[0030] Preferably, the photosensitive wet film needs to be cured after being coated by screen printing.
[0031] Preferably, the curing temperature is 150-200°C, for example, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0032] As a preferred technical solution of the present invention, the exposure process is performed in the following manner:
[0033] The copper-clad ceramic substrate to be roughened after the film lamination treatment is locally exposed.
[0034] It should be noted that the local exposure referred to in the present invention is a selective exposure process for the local area that needs to be exposed.
[0035] As a preferred technical solution of the present invention, the development process is carried out in the following manner:
[0036] The exposed copper-clad ceramic substrate to be roughened is developed using a weak alkaline solution.
[0037] Wherein, the weak alkaline solution is a sodium carbonate solution.
[0038] It should be noted that the concentration of the sodium carbonate solution in the present invention can be 10%.
[0039] As a preferred technical solution of the present invention, the roughening treatment is carried out in the following manner:
[0040] Roughening is performed by using a roughening liquid, sandblasting, or laser treatment.
[0041] When the roughening liquid is used for roughening, the roughening liquid adopts a sulfuric acid and hydrogen peroxide system solution.
[0042] It should be noted that the present invention adopts a sulfuric acid-hydrogen peroxide system solution, which is made of sulfuric acid and hydrogen peroxide in a certain ratio, and the concentration of sulfuric acid can be 4%; wherein the ratio of sulfuric acid to hydrogen peroxide is 1:2.
[0043] When sand blasting is used for roughening, the sand type used in the sand blasting is a glass bead type.
[0044] It should be noted that the present invention uses glass beads for sandblasting, which can make the sandblasting effect better and the sandblasting surface more uniform compared to other shapes (diamond, square, etc.).
[0045] Preferably, the mesh number of the glass beads is 400-600 mesh, for example, it can be 400 mesh, 420 mesh, 440 mesh, 460 mesh, 480 mesh, 500 mesh, 520 mesh, 540 mesh, 560 mesh, 580 mesh, 600 mesh, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] Preferably, the blasting pressure of the sandblasting treatment is 2-2.5 KPa, for example, it can be 2 KPa, 2.1 KPa, 2.2 KPa, 2.3 KPa, 2.4 KPa, 2.5 KPa, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In the present invention, the mesh number of the glass beads is 400-600 meshes and the blasting pressure of the sandblasting treatment is 2-2.5 KPa, because within this range, the sandblasting effect can be better. If it is not within this range, it may cause uneven sandblasting surface.
[0048] When laser processing is used for roughening, the laser may be a nanosecond laser.
[0049] It should be noted that the nanosecond laser in the present invention can be realized by using a nanosecond laser; preferably, a micro-ultraviolet nanosecond laser is used.
[0050] Preferably, the power of the laser processing is 180-200 W, for example, it can be 180 W, 182 W, 184 W, 186 W, 188 W, 190 W, 192 W, 194 W, 196 W, 198 W, 200 W, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0051] The power of the laser treatment in the present invention is 150-20W because the treatment effect can be better within this range. If it is not within this range, the treatment effect may be poor.
[0052] As a preferred technical solution of the present invention, the local coarsening method specifically includes:
[0053] The copper-clad ceramic substrate to be roughened is subjected to chemical cleaning treatment, film lamination treatment, exposure treatment, development treatment and roughening treatment in sequence to obtain a locally roughened copper-clad ceramic substrate;
[0054] Wherein, the exposure energy of the exposure treatment is 600-700mj;
[0055] The chemical cleaning process is carried out as follows:
[0056] The roughened copper-clad ceramic substrate is cleaned by using a cleaning liquid;
[0057] The cleaning liquid is an acidic degreasing agent, and the acidic degreasing agent includes any one of sulfuric acid, phosphoric acid, nitric acid or citric acid. The cleaning speed of the cleaning liquid is 1 to 1.5 mm / min, and the cleaning temperature of the cleaning liquid is 5 to 10°C.
[0058] The film pasting process is carried out as follows:
[0059] A photosensitive film is applied to the surface of the copper-clad ceramic substrate to be roughened after chemical cleaning;
[0060] The photosensitive film is a photosensitive dry film or a photosensitive wet film. The lamination temperature of the photosensitive dry film is 90-110° C., the lamination pressure of the photosensitive dry film is 5-10 KPa, the photosensitive wet film is laminated by screen printing, the mesh number of the screen printing is 200-300 meshes, and the photosensitive wet film needs to be cured after being laminated by screen printing, and the curing temperature is 150-200° C.;
[0061] The exposure process is performed as follows:
[0062] Partially exposing the copper-clad ceramic substrate to be roughened after film lamination;
[0063] The development process is carried out as follows:
[0064] The exposed copper-clad ceramic substrate to be roughened is subjected to a developing treatment using a weak alkaline solution;
[0065] Wherein, the weak alkaline solution is a sodium carbonate solution;
[0066] The roughening process is carried out as follows:
[0067] Roughening is performed by using a roughening liquid, or by using sandblasting, or by using laser treatment;
[0068] When the roughening liquid is used for roughening, the roughening liquid is a sulfuric acid and hydrogen peroxide system solution;
[0069] When sand blasting is used for roughening, the sand mold used in the sand blasting is a glass bead mold;
[0070] The mesh number of the glass beads is 400-600 meshes, and the blasting pressure of the sandblasting treatment is 2-2.5 KPa;
[0071] When laser processing is used for roughening, the laser is a nanosecond laser, and the power of the laser processing is 180-200W.
[0072] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0073] Compared with the prior art, the present invention has the following beneficial effects:
[0074] In the present invention, by limiting the steps, exposure parameters and sequence of the local roughening method of the surface of the copper-clad ceramic substrate, the roughness of the local position of the surface of the copper-clad ceramic substrate is greatly improved, and it is no longer necessary to roughen only the entire surface of the copper-clad ceramic substrate, thereby improving the roughening efficiency and the roughening quality. DETAILED DESCRIPTION
[0075] The technical solution of the present invention is further illustrated below through specific implementation methods.
[0076] Example 1
[0077] This embodiment provides a method for locally roughening the surface of a copper-clad ceramic substrate, wherein:
[0078] The copper-clad ceramic substrate to be roughened is subjected to chemical cleaning treatment, film lamination treatment, exposure treatment, development treatment and roughening treatment in sequence to obtain a locally roughened copper-clad ceramic substrate;
[0079] The exposure energy of the exposure process is 600 mj.
[0080] The chemical cleaning process is carried out as follows:
[0081] The roughened copper-clad ceramic substrate is cleaned with sulfuric acid at a cleaning speed of 1 mm / min.
[0082] The film processing is carried out as follows:
[0083] A photosensitive dry film is applied to the surface of the copper-clad ceramic substrate to be roughened after chemical cleaning.
[0084] The lamination temperature of the photosensitive dry film is 95°C, and the lamination pressure of the photosensitive dry film is 8KPa.
[0085] The exposure process is performed as follows:
[0086] The copper-clad ceramic substrate to be roughened after the film lamination treatment is locally exposed.
[0087] The development process is carried out as follows:
[0088] The exposed copper-clad ceramic substrate to be roughened is developed using a sodium carbonate solution.
[0089] The roughening process is performed as follows:
[0090] The surface is roughened using a sulfuric acid and hydrogen peroxide system.
[0091] Example 2
[0092] This embodiment provides a method for locally roughening the surface of a copper-clad ceramic substrate, wherein:
[0093] The copper-clad ceramic substrate to be roughened is subjected to chemical cleaning treatment, film lamination treatment, exposure treatment, development treatment and roughening treatment in sequence to obtain a locally roughened copper-clad ceramic substrate;
[0094] The exposure energy of the exposure process is 650mj.
[0095] The chemical cleaning process is carried out as follows:
[0096] Phosphoric acid is used to clean the roughened copper-clad ceramic substrate, and the cleaning speed of phosphoric acid is 1.2 mm / min.
[0097] The film processing is carried out as follows:
[0098] A photosensitive wet film is applied to the surface of the copper-clad ceramic substrate to be roughened after chemical cleaning.
[0099] The photosensitive wet film is laminated by screen printing, and the mesh number of the screen printing is 230 meshes. After the photosensitive wet film is laminated by screen printing, it needs to be cured, and the curing temperature is 170°C.
[0100] The exposure process is performed as follows:
[0101] The copper-clad ceramic substrate to be roughened after the film lamination treatment is locally exposed.
[0102] The development process is carried out as follows:
[0103] The exposed copper-clad ceramic substrate to be roughened is developed using a sodium carbonate solution.
[0104] The roughening process is performed as follows:
[0105] Sand blasting is used for roughening. The sand mold used for sand blasting is glass bead type, the mesh number of the glass bead type is 440 mesh, and the sand blasting pressure of the sand blasting is 2.2KPa;
[0106] Example 3
[0107] This embodiment provides a method for locally roughening the surface of a copper-clad ceramic substrate, wherein:
[0108] The copper-clad ceramic substrate to be roughened is subjected to chemical cleaning treatment, film lamination treatment, exposure treatment, development treatment and roughening treatment in sequence to obtain a locally roughened copper-clad ceramic substrate;
[0109] The exposure energy of the exposure process is 700 mj.
[0110] The chemical cleaning process is carried out as follows:
[0111] The roughened copper-clad ceramic substrate is cleaned with nitric acid at a cleaning speed of 1.5 mm / min.
[0112] The film processing is carried out as follows:
[0113] A photosensitive dry film is applied to the surface of the copper-clad ceramic substrate to be roughened after chemical cleaning.
[0114] The lamination temperature of the photosensitive dry film is 100°C, and the lamination pressure of the photosensitive dry film is 9KPa.
[0115] The exposure process is performed as follows:
[0116] The copper-clad ceramic substrate to be roughened after the film lamination treatment is locally exposed.
[0117] The development process is carried out as follows:
[0118] The exposed copper-clad ceramic substrate to be roughened is developed using a sodium carbonate solution.
[0119] The roughening process is performed as follows:
[0120] Laser treatment is used for roughening, the laser uses nanosecond laser, and the power of the laser treatment is 190W.
[0121] Example 4
[0122] This embodiment provides a method for local roughening of the surface of a copper-clad ceramic substrate. The difference from Embodiment 1 is that the lamination temperature of the photosensitive dry film is 80° C. Other parameters and implementation methods are the same as those of Embodiment 1.
[0123] Example 5
[0124] This embodiment provides a method for local roughening of the surface of a copper-clad ceramic substrate. The difference from Embodiment 1 is that the lamination temperature of the photosensitive dry film is 120° C. The other parameters and implementation methods are the same as those of Embodiment 1.
[0125] Example 6
[0126] This embodiment provides a method for local roughening of the surface of a copper-clad ceramic substrate, which is different from Embodiment 1 in that the mesh size of the screen used for screen printing is 180 meshes, and other parameters and implementation methods are the same as those of Embodiment 1.
[0127] Example 7
[0128] This embodiment provides a method for local roughening of the surface of a copper-clad ceramic substrate, which is different from Embodiment 1 in that the mesh number of the screen used for screen printing is 310 meshes, and other parameters and implementation methods are the same as those of Embodiment 1.
[0129] Example 8
[0130] This embodiment provides a method for local roughening of the surface of a copper-clad ceramic substrate, which is different from Embodiment 1 in that the sandblasting pressure of the sandblasting treatment is 1.9 KPa, and other parameters and implementation methods are the same as those of Embodiment 1.
[0131] Example 9
[0132] This embodiment provides a method for local roughening of the surface of a copper-clad ceramic substrate, which is different from Embodiment 1 in that the sandblasting pressure of the sandblasting treatment is 2.6 KPa, and other parameters and implementation methods are the same as those of Embodiment 1.
[0133] Example 10
[0134] This embodiment provides a method for local roughening of the surface of a copper-clad ceramic substrate, which is different from Embodiment 1 in that the power of the laser processing is 170 W, and the other parameters and implementation methods are the same as those of Embodiment 1.
[0135] Embodiment 11
[0136] This embodiment provides a method for local roughening of the surface of a copper-clad ceramic substrate. The difference from Embodiment 1 is that the power of the laser processing is 210 W, and the other parameters and implementation methods are the same as those of Embodiment 1.
[0137] Comparative Example 1
[0138] This comparative example provides a method for local roughening of the surface of a copper-clad ceramic substrate, which is different from Example 1 in that no chemical cleaning treatment is performed, and other parameters and implementation methods are the same as those of Example 1.
[0139] Comparative Example 2
[0140] This comparative example provides a method for local roughening of the surface of a copper-clad ceramic substrate, which is different from Example 1 in that the exposure energy of the exposure treatment is 580 mj, and the other parameters and implementation methods are the same as those of Example 1.
[0141] Comparative Example 3
[0142] This comparative example provides a method for local roughening of the surface of a copper-clad ceramic substrate, which is different from Example 1 in that the exposure energy of the exposure treatment is 720 mj, and the other parameters and implementation methods are the same as those of Example 1.
[0143] The surface roughness of the copper-clad ceramic substrate before and after local roughening in the above embodiments and comparative examples was tested according to the GB3505-1983 "Surface Roughness Terminology and Parameters". The results are shown in Table 1 below.
[0144] Table 1 Test results of copper-clad ceramic substrates before and after roughening in the examples and comparative examples
[0145] Roughness before local coarsening Roughness after local coarsening Example 1 0.73 1.21 Example 2 0.71 1.23 Example 3 0.74 1.19 Example 4 0.75 1.20 Example 5 0.78 1.18 Example 6 0.76 1.22 Example 7 0.75 1.21 Example 8 0.73 1.20 Example 9 0.73 1.19 Example 10 0.75 1.19 Embodiment 11 0.76 1.20 Comparative Example 1 0.77 1.1 Comparative Example 2 0.76 1.08 Comparative Example 3 0.73 1.11
[0146] From Table 1 above, we know that:
[0147] In summary, the present invention greatly improves the roughness of the local position of the surface of the copper-clad ceramic substrate by limiting the steps, exposure parameters and sequence of the local roughening method of the surface of the copper-clad ceramic substrate. It is no longer necessary to roughen the surface of the copper-clad ceramic substrate as a whole, thereby improving the roughening efficiency and the roughening quality.
[0148] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0149] The present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for local roughening of the surface of a copper-clad ceramic substrate, characterized in that: The local coarsening method comprises: The copper-clad ceramic substrate to be roughened is subjected to chemical cleaning treatment, film lamination treatment, exposure treatment, development treatment and roughening treatment in sequence to obtain a locally roughened copper-clad ceramic substrate; Wherein, the exposure energy of the exposure process is 600-700 mj.
2. The local roughening method according to claim 1, characterized in that: The chemical cleaning process is carried out as follows: The roughened copper-clad ceramic substrate is cleaned by using a cleaning liquid.
3. The local roughening method according to claim 2, characterized in that: The cleaning liquid is an acidic degreasing agent; Preferably, the acidic degreasing agent includes any one of sulfuric acid, phosphoric acid, nitric acid or citric acid; Preferably, the cleaning speed of the cleaning liquid is 1-1.5 mm / min.
4. The local roughening method according to any one of claims 1 to 3, characterized in that: The film pasting process is carried out as follows: A photosensitive film is applied to the surface of the copper-clad ceramic substrate to be roughened after chemical cleaning.
5. The local roughening method according to claim 4, characterized in that: The photosensitive film is a photosensitive dry film or a photosensitive wet film; Preferably, the lamination temperature of the photosensitive dry film is 90-110°C; Preferably, the lamination pressure of the photosensitive dry film is 5 to 10 KPa; Preferably, the photosensitive wet film is applied by screen printing; Preferably, the mesh number of the screen printing is 200 to 300 meshes; Preferably, the photosensitive wet film needs to be cured after being coated by screen printing; Preferably, the curing temperature is 150-200°C.
6. The local roughening method according to any one of claims 1 to 5, characterized in that: The exposure process is performed as follows: The copper-clad ceramic substrate to be roughened after the film lamination treatment is locally exposed.
7. The local roughening method according to any one of claims 1 to 6, characterized in that: The development process is carried out as follows: The exposed copper-clad ceramic substrate to be roughened is subjected to development treatment using a weak alkaline solution; Wherein, the weak alkaline solution is a sodium carbonate solution.
8. The local roughening method according to any one of claims 1 to 7, characterized in that: The roughening process is carried out as follows: Roughening is performed by using a roughening liquid, sandblasting, or laser treatment.
9. The local roughening method according to claim 8, characterized in that: When the roughening liquid is used for roughening, the roughening liquid is a sulfuric acid and hydrogen peroxide system solution; When sand blasting is used for roughening, the sand mold used in the sand blasting is a glass bead mold; Preferably, the mesh size of the glass beads is 400 to 600 mesh; Preferably, the sandblasting pressure of the sandblasting treatment is 2 to 2.5 KPa; When laser processing is used for roughening, the laser is a nanosecond laser; Preferably, the power of the laser processing is 180-200W.
10. The local roughening method according to any one of claims 1 to 9, characterized in that: The local coarsening method specifically includes: The copper-clad ceramic substrate to be roughened is subjected to chemical cleaning treatment, film lamination treatment, exposure treatment, development treatment and roughening treatment in sequence to obtain a locally roughened copper-clad ceramic substrate; Wherein, the exposure energy of the exposure treatment is 600-700mj; The chemical cleaning process is carried out as follows: The roughened copper-clad ceramic substrate is cleaned by using a cleaning liquid; The cleaning liquid is an acidic degreasing agent, and the acidic degreasing agent includes any one of sulfuric acid, phosphoric acid, nitric acid or citric acid. The cleaning speed of the cleaning liquid is 1 to 1.5 mm / min, and the cleaning temperature of the cleaning liquid is 5 to 10°C. The film pasting process is carried out as follows: A photosensitive film is applied to the surface of the copper-clad ceramic substrate to be roughened after chemical cleaning; The photosensitive film is a photosensitive dry film or a photosensitive wet film. The lamination temperature of the photosensitive dry film is 90-110° C., the lamination pressure of the photosensitive dry film is 5-10 KPa, the photosensitive wet film is laminated by screen printing, the mesh number of the screen printing is 200-300 meshes, and the photosensitive wet film needs to be cured after being laminated by screen printing, and the curing temperature is 150-200° C.; The exposure process is performed as follows: Partially exposing the copper-clad ceramic substrate to be roughened after film lamination; The development process is carried out as follows: The exposed copper-clad ceramic substrate to be roughened is subjected to a developing treatment using a weak alkaline solution; Wherein, the weak alkaline solution is a sodium carbonate solution; The roughening process is carried out as follows: Roughening is performed by using a roughening liquid, or by using sandblasting, or by using laser treatment; When the roughening liquid is used for roughening, the roughening liquid is a sulfuric acid and hydrogen peroxide system solution; When sand blasting is used for roughening, the sand mold used in the sand blasting is a glass bead mold; The mesh number of the glass beads is 400-600 meshes, and the blasting pressure of the sandblasting treatment is 2-2.5 KPa; When laser processing is used for roughening, the laser is a nanosecond laser, and the power of the laser processing is 180-200W.